Tris-(diphenylphosphoryl)benzamide lanthanides (III) trinitrates as a basis for creating the luminophore materials - Kariaka, N. S.; Trush, V. A.; Smola, S. S.; Fadeyev E. М.; Odynets, I. V.; Sliva, T. Y.; Amirkhanov V. М. (Reports of the National Academy of Sciences of Ukraine, 2016)
A row of new complexes Ln(HL)3(NO3)3 (Ln = La, Nd, Eu, Gd, Tb, Lu) with N-(diphenylphospho- ryl)benzamide (HL = C6H5CONHPO(C6H5)2) was synthesized. The mode of coordination of ligands and the structure of coordination compounds are proposed on the basis of the elemental analysis and data of IR, NMR, and absorption spectroscopies. The lowest triplet state of ligands in the complexes was found from the gadolinium complex phosphorescence spectrum. According to the luminescence investigations, the emission lifetime of the europium complex equals 1.66 ms, and the total emission quantum yield is 44%. Thermal gravimetric analysis showed the compound Eu(HL)3(NO3)3 thermal stability to 150 ◦C.